Laparoscopic adrenalectomy - Peyroulou, Alfredo; Salom, Andrés; Harguindeguy, Martín; Taroco, Luis; Ardao, Gonzalo; Broli, Fabiana (Cirugía del Uruguay, 2005)
The paper presents the case of a fema/e patient who carried an aldosterone-secreting tumor of adren al cortex. In the ana/ysis of diagnosis and parac/ inical examinations there is particular reference to the /aparoscopic surgery mode of treatment. Diagnosis should be estab/ished on the basis of clinica/ and laboratory tests (hypopotassemia and hypera/dosteronism). Tumor topography was confirmed through CT sean, MRI and Scintiscan in left adrenal cortex. Resection was consequently made through /aparoscopic surgery. The patient's evo/ution was excel/ent from the surgica/ viewpoint, with / /e veis of b/ood pressure, potassium and a/dosterone returned to normal.